2014
DOI: 10.1155/2014/603871
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response, Safety, and Survival and Quality of Life Outcomes for Advanced Colorectal Cancer Patients Treated with Dendritic Cell Vaccine and Cytokine-Induced Killer Cell Therapy

Abstract: Purpose. To determine the immune response after dendritic cell (DC) vaccine and cytokine-induced killer cells (CIK) therapy and assess its associated toxicity, survival benefit, and changes in the quality of life (QOL) of advanced colorectal cancer (CRC) patients. Methods. We recruited 100 patients with unresectable CRC orrelapsed CRC after surgery who received DC vaccine and CIK cells (group immunotherapy, group I), and, as a control, 251 patients who had similar characteristics and underwent similar treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 28 publications
(19 reference statements)
1
46
0
Order By: Relevance
“…Other studies suggest that the cytotoxicity of CIK cells can be enhanced and improved by DC vaccination and when transfected with IL-2 gene or activated by Retro Nectin, these CIK cells demonstrate a higher proliferation rate and efficient cytotoxic activity. 54,56,[58][59][60][62][63][64]67,68,72,75,84 In general, all these published studies have demonstrated that CIK cell-based immunotherapy utilizes the body's natural ability to eliminate tumor cells by stimulating and restoring the ability of the immune system to recognize and kill tumor cells. In contrast to conventional therapeutic strategies, the application of CIK cells is associated with minimal side effects and no severe adverse events have been reported.…”
Section: Clinical Usementioning
confidence: 99%
“…Other studies suggest that the cytotoxicity of CIK cells can be enhanced and improved by DC vaccination and when transfected with IL-2 gene or activated by Retro Nectin, these CIK cells demonstrate a higher proliferation rate and efficient cytotoxic activity. 54,56,[58][59][60][62][63][64]67,68,72,75,84 In general, all these published studies have demonstrated that CIK cell-based immunotherapy utilizes the body's natural ability to eliminate tumor cells by stimulating and restoring the ability of the immune system to recognize and kill tumor cells. In contrast to conventional therapeutic strategies, the application of CIK cells is associated with minimal side effects and no severe adverse events have been reported.…”
Section: Clinical Usementioning
confidence: 99%
“…The cells were cultured overnight, then adherent cells (including monocytes) and suspension cells (including lymphocytes) were collected separately (14)(15)(16).…”
Section: Preparation Of Cellsmentioning
confidence: 99%
“…Useful approaches of ACT for the treatment of CRC include the use of dendritic cell (DC) pulsed with tumor-associated antigens (TAAs) and cytotoxic T lymphocytes (CTLs) activated using those DCs (6)(7)(8)(9). However, these treatment strategies are unable to generate sufficient antitumor immune responses.…”
Section: Introductionmentioning
confidence: 99%